CAMTA1 gene affects the ischemia-reperfusion injury by regulating CCND1 - Liu, Yang; Shang, Guohui; Zhang, Xuran; Liu, Fuyong; Zhang, Chi; Li, Zhihao; Jia, Jing; Xu, Yan; Zhang, Zhaojing; Yang, Shangdong; Zhou, Baixue; Luan, Yingying; et al. (Frontiers in Cellular Neuroscience, 2022)
Epigenetic modulations lead to changes in gene expression, including DNA methylation, histone modifications, and noncoding RNAs. Over recent years, epigenetic modifications have related to the pathogenesis of different types of cancer, cardiovascular disease, and other diseases. Emerging evidence indicates that DNA methylation could be associated with Ischemic Stroke (IS) and play a role in pathological progression, but the underlying mechanism has not yet been fully understood. Herein, we used Human Methylation 850K BeadChip to analyze the differences of gene methylation status in the peripheral blood samples from two groups (3 IS patients vs. 3 healthy controls). According to their bioinformatics profiling，we found 278 genes with significantly different methylation levels. 7 genes with the most considerable methylation modifications were validated in two expanded groups (100 IS patients vs. 100 healthy controls). The CAMTA1 gene had the most different methylation change in patients compared to the controls. To understand the CAMTA1 function in stroke, we generated CAMTA1 knockout in SH-SY5Y cells. RNA seq results in CAMTA1 knockout cells revealed that the pathways and gene set enrichments involved in cellular proliferation and cell cycle. Furthermore, a series of experiments demonstrated that in the OGD/R model system, the expression of cyclin D1, an essential regulator of cell cycle progression, was increased in SH-SY5Y CAMTA1 KO cells. Increasing evidence demonstrated that ischemic stress could inappropriately raise cyclin D1 level in mature neurons. However, the molecular signals leading to an increased cyclin D1 level are unclear. Our findings demonstrate for the first time that CAMTA1 gene could regulate cyclin D1 expression and implicate a role in stroke.